2023
DOI: 10.1002/anie.202314185
|View full text |Cite
|
Sign up to set email alerts
|

Co−Co Dinuclear Active Sites Dispersed on Zirconium‐doped Heterostructured Co9S8/Co3O4 for High‐current‐density and Durable Acidic Oxygen Evolution

Ligang Wang,
Hui Su,
Zhuang Zhang
et al.

Abstract: Developing cost‐effective and sustainable acidic water oxidation catalysts requires significant advances in material design and in‐depth mechanism understanding for proton exchange membrane water electrolysis. Herein, we developed a single atom regulatory strategy to construct Co‐Co dinuclear active sites (DASs) catalysts that atomically dispersed zirconium doped Co9S8/Co3O4 heterostructure. The X‐ray absorption fine structure elucidated the incorporation of Zr greatly facilitated the generation of Co‐Co DASs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…The direct oxo–oxo coupling mechanism (DOOC) can be achieved in dinuclear active-site catalysts, for instance, dinuclear Co–Co sites in Co 9 S 8 /Co 3 O 4 . 61 O–O coupling occurs at the heterointerface between Au clusters and NiFe-hydroxide, which is denoted as interfacial DOOC. 62 Very recently, Ru atoms embedded into cation vacancies of the Co 3 O 4 surface can switch the reaction pathway from LOM to optimized AEM by activating the proton donor–acceptor mechanism (PDAM), elucidating the acidic oxygen evolution.…”
Section: Fundamentals and Bottleneck Of Electrochemical Water Splittingmentioning
confidence: 99%
“…The direct oxo–oxo coupling mechanism (DOOC) can be achieved in dinuclear active-site catalysts, for instance, dinuclear Co–Co sites in Co 9 S 8 /Co 3 O 4 . 61 O–O coupling occurs at the heterointerface between Au clusters and NiFe-hydroxide, which is denoted as interfacial DOOC. 62 Very recently, Ru atoms embedded into cation vacancies of the Co 3 O 4 surface can switch the reaction pathway from LOM to optimized AEM by activating the proton donor–acceptor mechanism (PDAM), elucidating the acidic oxygen evolution.…”
Section: Fundamentals and Bottleneck Of Electrochemical Water Splittingmentioning
confidence: 99%
“…Thus, the AEM pathway could be further classified into the new type AEM which occurred over synergistic sites to break the scaling relationships and the classic type at a single site with limited performance (Figure 3c). 38 Besides the peaks attributed to *OOH/*OO, other intermediates such as M�O and *O have been monitored via SR-FTIR to analyze the specific process of the OER. For oxygen species adsorbed over Ir-based catalysts, the adsorption peak of the O−O species was always located between 700 and 900 cm −1 , while M�O tended to be observed between 800 and 1000 cm −1 .…”
Section: Sr-ftirmentioning
confidence: 99%
“…By comparing the stretching vibration of *OOH, the peak of 1090 cm –1 could be attributed to the O–O bond formed at dual Co–Co sites (Figure b), while the peak of 1024 cm –1 was considered the Co–*OOH intermediates. Thus, the AEM pathway could be further classified into the new type AEM which occurred over synergistic sites to break the scaling relationships and the classic type at a single site with limited performance (Figure c) …”
Section: In Situ Infrared Spectroscopy For Configuration Of the Inter...mentioning
confidence: 99%
“…Typically, the metal center in SACs is stabilized and regulated by the coordination of the heteroatom (N, S, O, P, etc.) in the support matrix. The direct pyrolysis of metal-zeolite imidazolate frameworks (M-ZIFs) is currently believed to be a significant method for the preparation of metal–nitrogen-carbon SACs (M/NC-SACs) with the symmetric coordination of N atoms. It is noteworthy that compared with symmetrical M-NC, asymmetric M-NPC constructed by doping P atoms with a weaker electronegativity than N atoms can further modulate the electronic structure of the metal center and improve its catalytic efficiency. For example, our recent study has demonstrated that the superior peroxidase-like activity of FeN 3 P-SAzyme was attributed to the electron-donating P atoms, which reduced the positive charge of the metal Fe center .…”
Section: Introductionmentioning
confidence: 99%